2013
DOI: 10.1007/s10753-013-9790-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and Pharmacokinetic Studies with Vitamin D-loaded Nanoemulsions in Asthma Model

Abstract: Vitamin D (VD) was studied for its anti-inflammatory activities with prepared VD-loaded nanoemulsions (VDNM) in ovalbumin-induced asthmatic mice in this paper. In this study, we prepared VDNM for the delivery of VD from the established composition of solid self-emulsifying drug delivery systems (sSEDDS) by spray-drying technique and evaluated its bioavailability (BA) and anti-inflammatory activities in experimental allergic asthma. After the mice were treated orally with VD or VDNM, the plasma 25(OH) D levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A higher serum MPO level is associated with the systemic inflammation related to CV disease 80 and vitamin D3 treatment significantly reduced MPO. 81 This may refer to its important inhibitory influence on this inflammatory pathway. 82…”
Section: Discussionmentioning
confidence: 99%
“…A higher serum MPO level is associated with the systemic inflammation related to CV disease 80 and vitamin D3 treatment significantly reduced MPO. 81 This may refer to its important inhibitory influence on this inflammatory pathway. 82…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the absorption capacity of Aerosil 200, a colloidal silica, which has been adopted as one of the most commonly used solid carriers in previous studies, 8,[26][27][28] was also measured. When the ratio of Aerosil 200 to liquid SEDDS increased from 1:1 to 1:2 (w/w), the powdered solid samples were changed to sticky aggregates.…”
Section: Preparation Of Ssedds Matrixmentioning
confidence: 99%
“…The observed protective effect of VD on oxidant forces is consistent with existing data in the literature. One study reported that oral VD nanoemulsion therapy decreased oxidant species' activity in the serum of mice with airway inflammation [51]. In another study, VD decreased ROS when added to human bronchial epithelial cell culture, thus alleviating lipopolysaccharide-induced oxidative stress [52].…”
Section: Discussionmentioning
confidence: 99%